Effectiveness of red clover in alleviating menopausal symptoms: a 12-week randomized, controlled trial. (August 2015) - Shakeri, F.; Taavoni, S.; Goushegir, A.; Haghani, H.
Abstract Objectives Menopausal women are interested in alternative therapy to alleviate climacteric symptoms. This study aimed to investigate the effect of red clover on the severity of menopausal symptoms. Methods This randomized, placebo-controlled, clinical trial included 72 healthy postmenopausal women, who were randomly divided into intervention and placebo groups. Women in the intervention group received two capsules containing 40 mg dried leaves of red clover daily for 12 weeks, while those in the control group received two capsules containing 40 mg starch daily for 12 weeks. Outcome measures of this study were menopausal symptoms determined using the Menopause Rating Scale (MRS) at baseline and at the end of the study. Sociodemographic data of the included women were collected using a questionnaire. Results No significant differences were observed between the two groups with respect to the demographic characteristics and menopausal symptoms before the intervention. At the end of the study, the total score on the MRS decreased from 20.41 to 10.08 in the intervention group and from 20.77 to 17.20 in the control group. This decrease in the total score was attributed to the scores of vegetative somatic and psychological categories of menopausal symptoms. Thus, a remarkable difference was observed in the severity of the menopausal symptoms (95% confidence interval, p = 0.0001). Conclusion These results indicated that, compared to placebo, dried leaves of red clover were more effective in reducing the severity of menopausal symptoms in postmenopausal women.